Science and Math Education Reform. Hearing before the Committee on Governmental Affairs. United States Senate, One Hundred Second Congress, Second Session (Cleveland, Ohio, July 7, 1992) - Congress of the U.S., Washington, DC. Senate Committee on Governmental Affairs; Congress of the U.S., Washington, DC. Senate Committee on Governmental Affairs ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
This document presents a field hearing of the Governmental Affairs Committee to examine the current reform efforts in science and mathematics education at the federal and state levels, focusing specifically on the experiences of Ohio. Nine witnesses representing various educational levels presented testimony concerning mathematics and science education initiatives in Ohio. Initiatives and issues discussed included: (1) the Ohio Proficiency Test; (2) Project Discovery, a project focusing on preparing middle school students to think critically and solve problems; (3) the National Center for Science Teaching and Learning; (4) curriculum reform; (5) societal factors influencing reform; (6) collaboration among the higher education, public education, and business sectors; (7) the B-WISER Institute, a summer camp and follow-up program that empowers young women to achieve in science; and (8) the under-representation of minorities and women in mathematics and science. Appendices contain copies of prepared statements by the witnesses and other participants. (MDH)
Availability: U.S. Government Printing Office, Superintendent of Documents, Congressional Sales Office, Washington, DC 20402.
ERIC Note: Contains pages of extremely small type.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Demonstration Programs; Educational Change; Elementary Secondary Education; Federal Government; Females; Hands On Science; HANDS ON SCIENCE; Hearings; Mathematics Education; Minority Group Children; School Business Relationship; Science Education; Ninth Grade Proficiency Test -- Project Discovery; Congress 102nd -- Hands on Science -- Ohio; Legal/Legislative/Regulatory Materials